Simplified Bishop score including parity predicts successful induction of labor. (August 2016) - Ivars, Joanna; Garabedian, Charles; Devos, Patrick; Therby, Denis; Carlier, Sabine; Deruelle, Philippe; Subtil, Damien
Abstract: Objective: Our objectives were to confirm the predictiveness of parity for successful labor induction and propose an improvement in the Bishop's score to take parity into account and simultaneously simplify the original Bishop score. Study design: Retrospective study of 326 deliveries induced by oxytocin and amniotomy before prostaglandins between January 1, 1987, and June 30, 1988. We conducted a univariate and then a multivariate analysis of the relation between successful labor induction – defined by vaginal delivery- and the components of Bishop's score and parity. Results: Nulliparous accounted for 38% of the studied population. The mean Bishop at induction was 5.75 ± 1.4. Fetal station, cervical effacement, and parity were the only factors associated with the success of induction in this study. Removing the cervical position and consistency from the score as well as adding parity significantly improved the prediction of success (ROC curves, AUC 0.88 vs 0.68, p  < 0.001). By taking 5% as the maximum risk of induction failure, a cutoff point of 4 for the new score makes it possible to induce labor in 90% of the women that were considered in the study (vs 26% or 60%, according to whether the cutoff point of the original Bishop's score is set, respectively, at 7 or 6, p  < 0.001). Conclusion: Cervical position and consistency are not necessary for predicting successful labor induction by oxytocin and amniotomy. We confirmed the usefulness of a simplified Bishop score that considers parity.